Experience in using the polymerase chain reaction method for diagnosis of measles in the Russian Federation - T. L. Zamotaeva; E. A. Cherkashin; M. A. Ninalalov; Zh. B. Ponezheva; V. G. Akimkin (Лечащий Врач)
Background. The epidemic situation regarding measles both in Russia and in the world makes it extremely urgent to introduce highly sensitive molecular methods, such as polymerase chain reaction, into diagnostics, in addition to existing serological ones. This paper describes the experience of using the polymerase chain reaction method for diagnosing measles in the Russian Federation using the example of the Republic of Dagestan.Objective. Early detection of measles virus using a highly sensitive polymerase chain reaction method in various types of biomaterial.Materials and methods. The study was carried out using the polymerase chain reaction method on biomaterial samples from 208 patients diagnosed with measles and 30 apparently healthy volunteers in the control group. The diagnosis of measles was established based on a combination of clinical manifestations and confirmed by the results of laboratory testing with the detection of IgM class antibodies using enzyme linked immunosorbent assay.Results. Patients admitted to the hospital before 4 days from the onset of the rash were found to be positive by polymerase chain reaction testing for measles virus RNA. The viral load in urine samples and swabs from the nasopharynx and oropharynx was 103-109 GE/ml, of which in 67.5% of cases it was 106-109 GE/ml; while a much smaller amount of viral RNA was detected in the blood serum – 103-105 GE/ml.Conclusion. The possibility of early detection of measles using the polymerase chain reaction method has been shown, which will improve the process of differential diagnosis of diseases that have a similar clinical picture when introducing polymerase chain reaction tests for measles into practical healthcare. This approach involves testing not only sick people, but also contact persons.